[Small brass band posing for a casual picture outside of a building] (1946)
The band the "Hungry Five," a comic musical group. Left to right: Bob McCormick, Donald Lansing, Dan Jones, Bob Roney, and Everett Miller. Published in the 1946 El Rodeo Yearbook.